Paradigm shift in clinical trial regulations in India - Sandeep Lahiry; Rajasree Sinha; Shouvik Choudhury; Ayan Mukherjee; Suparna Chatterjee (Indian Journal of Rheumatology)
India has the potential to contribute meaningfully to global clinical drug development. A critical enabler to achieve this potential is a balanced, predictable, and scientifically robust regulation involving clinical studies. In the past few years, the country's regulatory milieu has witnessed a positive transformation to favour ethical conduct of clinical trials, while appropriately supporting patient safety. Numerous amendments to existing policies governing the conduct of clinical studies are predicted to bring a paradigm shift in the overall regulatory scenario. In such view, it is important for us as academicians, to be abreast of such changes. We, therefore, discuss major regulatory highlights involving clinical research in India.